2020
DOI: 10.3389/fendo.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

PCOS-GWAS Susceptibility Variants in THADA, INSR, TOX3, and DENND1A Are Associated With Metabolic Syndrome or Insulin Resistance in Women With PCOS

Abstract: Polycystic ovary syndrome is characterized by reproductive and metabolic disturbances throughout the female lifespan. Therefore, this study aimed to determine whether genome-wide association studies (GWAS)-identified risk variants for PCOS could confer risk of metabolic syndrome (MS) or insulin resistance (IR). Fifteen independent SNPs mapping to 11 GWAS loci genotyped in a total of 2,082 Han Chinese women independent of previous GWAS and phenotype-genotype correlations were assessed. The CC group for rs124786… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
(56 reference statements)
0
30
0
Order By: Relevance
“…In addition, some PCOS candidate genes, such as thyroid adenoma associated ( THADA ) and insulin receptor ( INSR) , have been associated with metabolic syndrome and impaired glucose regulation in PCOS and type 2 diabetes [ 77 ], suggesting genetic contributions to metabolic dysfunction in women with PCOS. Moreover, in a recent Mendelian randomization study, gene variants associated with high bioavailable (unbound) circulating T levels were also linked with PCOS and type 2 diabetes [ 78 ], providing an additional causal role for female hyperandrogenism in the onset of both disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some PCOS candidate genes, such as thyroid adenoma associated ( THADA ) and insulin receptor ( INSR) , have been associated with metabolic syndrome and impaired glucose regulation in PCOS and type 2 diabetes [ 77 ], suggesting genetic contributions to metabolic dysfunction in women with PCOS. Moreover, in a recent Mendelian randomization study, gene variants associated with high bioavailable (unbound) circulating T levels were also linked with PCOS and type 2 diabetes [ 78 ], providing an additional causal role for female hyperandrogenism in the onset of both disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The reality is that a C/T polymorphism in the tyrosine kinase domain of INSR gene can be a susceptible variant for PCOS ( Table 2 ). Furthermore, the rs2059807 and rs1799817 in INSR gene were significantly associated with IR in PCOS women in different populations [ 74 , 78 – 80 ]. In fact, INSR mediates the effect of insulin resistance on PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to epigenetic studies, many studies have been conducted to decipher the genetic nature of PCOS. In addition, a number of studies have looked at the link between significant clinical aspects of PCOS and GWAS-identified variants in the last several years [ 25 , 26 ]. The goal of the PCOS GWAS loci analysis is to provide insight on the mechanism by which the risk of SNPs may impact the aetiology of PCOS status and, ultimately, to improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Following these studies, it appears that the genes DENND1A and TOX3, as well as the genes LHCGR, AMH, AMHR2, THADA, and INSR, are the most important genes in the susceptibility of PCOS. Genetic variations in the previously mentioned genes may be involved in several pathways, including insulin resistance, the dysregulation of androgen and gonadotrophins, and metabolic disorder-related pathways in PCOS pathogenesis [ 25 , 26 , 27 ]. There is ample evidence that polycystic ovary syndrome is an intrinsic syndrome, and in most of its clinical symptoms such as obesity and diabetes, traces of genetic variation might be seen [ 28 ].…”
Section: Introductionmentioning
confidence: 99%